Designing and Manufacturing the Press Tool of Air Bending V Brake - Rusdi Nur; Muhammad Arsyad Suyuti; Muhammad Iswar (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Nowadays, the metal forming process in the welding machinery and machinery industry is developing very rapidly, especially in the bending process. The buckling process is a metal formation which generally uses sheet plates or rods from both ferrous and non-ferrous metals by bending, which in the bending process will cause a stretching or stretching on the neutral axis of the field along the bending area and producing a straight bending line. Appropriate technology machines have been widely used to increase productivity, efficiency, and effectiveness in the production process for community efforts. One of the appropriate technologies that can be applied in buckling is a tool equipped with a press tool. Press tool is one type of tool for the formation, cutting and bending of products from the base material of sheet plates whose operation uses a press machine. In this study, a V brake bending tool has been produced which has a capacity that is bending line length 300 mm, bending width 33 mm, spring height 110 mm, free step distance 19 mm, spring load received 263,820 N and material capacity that can be bent is a thickness of 3 mm, the punch angle used is 85⁰ with a punch radius used which is 1.5 mm while the die angle is 85⁰